The Effectiveness of Risk Management and Business Performance: SMEs in Bangkok, Thailand - Tanapol Kortana (International Journal of Supply Chain Management, 2019)
Objective: To test the effectiveness of the risk management model composing of 5 variables on the business performance of SMEs in Bangkok, Thailand. These variables were strategic, financial, operational, compliance risks, and the balanced scorecard, respectively. Methods: The research is undertaken based on a quantitative research methodology in which the data collection has been achieved through self-administered questionnaires from n = 400 participants. The item-objective congruence value test was used to assess the questionnaire validity at the design stage, on a pilot sample of 3 experts. Cronbach Alpha was used to determine validity. Findings: The 5-factor model was found to determine 61.2% of the observed effect with a confidence level of 99%. Implications: Practitioners in SMEs are advised to implement the balanced scorecard and risk management strategies in their companies. Supporting governmental initiatives increasing risk management literacy are welcomed. Academics may further develop this field by identifying specific risk management strategies for Thailand.